الاسم بين العربية والانجليزية دراسة تقابلية تطبيقية عند طلبة قسم الترجمة بجامعة البصرة مركز دراسات البصرة والخليج العربي جامعة البصرة، العراق: Amidst the Arabic and English Nouns: An applied contrastive study for the students of the translation department at the University of Basra - Al Abdullah, Murad Hameed (SIBAWAYH Arabic Language and Education, 2021)
لكل لغة انسانية مجموعة من العناصر الرئيسة التي يعتمد عليها في البناء والتركيب اللغوي، ولكل منها مجموعة من الميزات التي تميزها عن العناصر اللغوية الاخرى، فالعربية والانجليزية تميزتا كونهما تمتلكان العناصر نفسها لكن لكل منها ترتيبها وميزاتها الخاصة، بحيث تميزت إحداها عن الاخرى، والاسم يعد أحد أهم أركان البناء اللغوي في العربية والانجليزية والذي يعد الركيزة الاساس في تكوين الجملة في اللغتين خصوصا ماتسمى بالجملة الاسمية، فضلا عند كونه الجزء المكمل لبناء الجملة الفعلية، وعند عملية البحث كان لزاما ان نقوم بتحديد أهم ميزات هذا القسم الذي يعد اول أقسام الكلام في اللغتين العربية والانجليزية (Parts of speech) الا وهو الاسم (Noune).Every human language has a set of the main elements on which it depends in the construction and linguistic structure, each of them has a set of features that distinguish it from other linguistic elements. The most important pillars of linguistic construction in Arabic and English, which is the basis for the formation of the sentence in the two languages, especially the so-called nominal sentence, as well as when it is the complementary part of the construction of the actual sentence. And the English (Parts of speech), which is the (Noune).